2022
DOI: 10.1039/d2ta00834c
|View full text |Cite
|
Sign up to set email alerts
|

A dendrite-suppressed and utilization-improved metallic Li anode enabled by lithiophilic nano-Pb decoration on carbon cloth

Abstract: The commercialization of Li metal anode has been long hindered by uncontrolled dendrite growth, infinite volume expansion and poor Li metal utilization. Herein, we achieve a uniform nano-Pb decoration on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…2d ), the ultrafast charge transfer kinetics at the interface can also be ascribed to the easier Na diffusion in the Na 15 Pb 4 alloy than in metallic Na, a phenomenon widely confirmed in Li ( e.g. , Li–Pb 34 ) and Na ( e.g. , Na–Sn 38 ) alloy anodes.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…2d ), the ultrafast charge transfer kinetics at the interface can also be ascribed to the easier Na diffusion in the Na 15 Pb 4 alloy than in metallic Na, a phenomenon widely confirmed in Li ( e.g. , Li–Pb 34 ) and Na ( e.g. , Na–Sn 38 ) alloy anodes.…”
Section: Resultsmentioning
confidence: 76%
“…S2, † clearly disclosing the phase transformation of LAT to PbO, and nally to Pb/C. [32][33][34] The existence of metallic Pb is conrmed using the XRD pattern acquired on the surface of a Pb/C@NZSP pellet (Fig. 1e).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As far as conventional SMBs are concerned, we have shown that a great deal of research was conducted to develop 3D sodiophilic hosts for Na metal anodes, with significant performance achieved. However, it should be noticed that the attention to cell-level energy density, i.e., concerning the host and wetting agent weights, utilization of infused Na, and N/P ratios for full-cell demonstration, is not enough [84,92]. We note that much of the literature does not report cell-level energy densities and cost analyses because the field is still in its infancy compared to Li-ion.…”
Section: Discussionmentioning
confidence: 93%
“…The loading of the LiFePO 4 cathode used here is two to three times higher than that of previously reported LiFePO 4 cathodes, whereas the N/P ratio is much lower. [55][56][57][58][59] Due to the improved electrochemical activity and suppressed side reactions of spherical Li, excellent Li-metal cell performance is achieved, resulting in a high-capacity retention of 94.8% after 110 cycles. This is better than the whisker Li|LFP full cell, which shows a sharp capacity degradation after 90 cycles (Figure 5d).…”
Section: Low N/p Ratio High Energy Density Full Cellsmentioning
confidence: 99%